DYNAMIC ARCHIVE DISTRIBUTION APPLICATION FOR PT. PERUSAHAAN GAS NEGARA TBK AREA SEMARANG - Sulistiyo Mutiara Jaya; Iwan Hermawan; Suwardi Suwardi (Politeknik Negeri Semarang, 2018)
PT. Perusahaan Gas Negara Tbk (PGN) is a company engaged in the field of natural gas transmission and distribution in Indonesia. One of the sales offices is in Semarang, Central Java. Administrative activities in a service company like PGN really need to be considered. One such activity is the management and distribution of archives. Archives are very useful for companies in various activities. The purpose of this research is to provide convenience in the management and distribution of archives at PGN area Semarang. This study designed a dynamic archive distribution application using software Microsoft Visual FoxPro 9.0 with rapid application development (RAD) research methods. The results of this study provide efficiency in managing archives such as input, retrieval, and distribution of archives at PGN area Semarang.